2014
DOI: 10.1124/jpet.114.218081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Benign and Reversible Unconjugated Hyperbilirubinemia Observed with Faldaprevir Administration in Hepatitis C Virus Patients

Abstract: Faldaprevir, an investigational agent for hepatitis C virus treatment, is well tolerated but associated with rapidly reversible, dosedependent, clinically benign, unconjugated hyperbilirubinemia. Multidisciplinary preclinical and clinical studies were used to characterize mechanisms underlying this hyperbilirubinemia. In vitro, faldaprevir inhibited key processes involved in bilirubin clearance: UDP glucuronosyltransferase (UGT) 1A1 (UGT1A1) (IC 50 0.45 mM), which conjugates bilirubin, and hepatic uptake and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
(56 reference statements)
6
21
0
Order By: Relevance
“…Overall, the safety profile observed in this study was consistent with that reported in the faldaprevir clinical trial program in subjects without renal impairment (13)(14)(15)(16)(17). Increased levels of indirect bilirubin were not accompanied by elevations of other markers of liver toxicity, and these clinically irrelevant, transient indirect bilirubin increases are a well-known effect of treatment with faldaprevir, which is an inhibitor of UGT1A1 and hepatic uptake transporters (35).…”
Section: Discussionsupporting
confidence: 74%
“…Overall, the safety profile observed in this study was consistent with that reported in the faldaprevir clinical trial program in subjects without renal impairment (13)(14)(15)(16)(17). Increased levels of indirect bilirubin were not accompanied by elevations of other markers of liver toxicity, and these clinically irrelevant, transient indirect bilirubin increases are a well-known effect of treatment with faldaprevir, which is an inhibitor of UGT1A1 and hepatic uptake transporters (35).…”
Section: Discussionsupporting
confidence: 74%
“…In vitro data have shown that CYP3A4 is one of the key enzymes involved in EE/LNG oxidative metabolism in the liver (21), and thus, a likely mechanism for the increased exposure is via altered EE elimination due to the inhibition of CYP3A4 by faldaprevir. Inhibition of UGT1A1 by faldaprevir, reported by Sane and colleagues (15), may affect glucuronidation of synthetic hormones in the liver and could contribute to the increased exposure of EE and LNG reported here.…”
Section: Discussionsupporting
confidence: 51%
“…In vivo data suggest that with a twice-daily (BID) dose of 240 mg in healthy volunteers, faldaprevir is a weak inhibitor of CYP2C9 and a moderate inhibitor of CYP3A4 (13), whereas a dose of 120 mg faldaprevir QD in HCV patients resulted in weak inhibition of CYP3A4 and had no effect on CYP2C9 (14). In vitro data also suggest that faldaprevir inhibits P-glycoprotein (P-gp), UDP-glucuronosyltransferase (UGT1A1), and CYP2C8 (14,15). EE, which has a terminal half-life of 10 to 20 h, is metabolized in the liver by hydroxylation mediated by CYP3A4 and CYP2C9, followed by glucuronidation by UGT1A1 (12).…”
Section: Hronic Hepatitis Caused By Hepatitis C Virus (Hcv) Infectimentioning
confidence: 99%
“…2). Faldaprevir inhibits the bilirubin conjugation enzyme, UGT1A1, and to a lesser extent the bilirubin transporters, OATP1B1, and MRP2 [30]. Increases in bilirubin have also been observed with simeprevir; however, this is predominantly driven by inhibition of OATP1B1 and MRP2 [31].…”
Section: Discussionmentioning
confidence: 99%